Project management : the managerial process - Larson, Erik W.; Gray, Clifford F. (New York : McGraw Hill Education, 2011)
This book covers concepts and skills that are used by managers to propose, plan, secure resources, budget, and lead project teams to successful completions of their projects.
Chapter 1. Modern project management -- 2. Organization strategy and project selection -- 3. Organization: structure and culture -- 4. Defining the project -- 5. Estimating project times and costs -- 6. Developing a project plan -- 7. Managing risk -- 8. Scheduling resources and costs -- 9. Reducing project duration -- 10. Leadership: being an effective project manager -- 11. Managing project teams -- 12. Outsourcing: managing interorganization relations -- 13. Progress and performance measurement and evaluation -- 14. Project closure -- 15. International projects -- 16. Oversight -- 17. An introduction to Agile project management -- 18. Project management career paths -- Appendix One. Solutions to selected exercises -- Appendix Two. Computer project exercises.
Includes index.
Keywords: PROJECT MANAGEMENT